2010
DOI: 10.1002/nau.20943
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' views on the feasibility of surgical randomized trials in urogynecology: Results of a questionnaire survey

Abstract: This study highlights the difference between collective and individual equipoise and their impact upon surgical trials. Clinicians held strong views preventing them from regarding the study favorably. Difficulty with relinquishing control over choice of procedure appeared central. These findings support the growing evidence in favor of detailed qualitative pilot work for surgical trials. The role of expertise-based randomization deserves further consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Surgeons’ preferences are a well-recognised and accepted barrier to their participation in trials [10,55-58] but investigators in previous studies have not tried to understand these preferences, how they are formed or the evidence on which they are based, although there is some data to suggest that surgeons’ understanding is limited [56]. By contrast, several studies have explored the basis of patients’ treatment preferences [59-62].…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons’ preferences are a well-recognised and accepted barrier to their participation in trials [10,55-58] but investigators in previous studies have not tried to understand these preferences, how they are formed or the evidence on which they are based, although there is some data to suggest that surgeons’ understanding is limited [56]. By contrast, several studies have explored the basis of patients’ treatment preferences [59-62].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously IUT is widely established in clinical practice and the absence of this investigation prior to offering surgery is a potential barrier to clinicians' willingness to randomise their patients. Clinician surveys in other urogynaecology research have identified clinicians' views of perceived benefit and complications of the two arms as impacting participation [14]. Women may also not see the benefit of testing a test, believing that the results of any available test must guide their clinician and themselves to the most appropriate management.…”
Section: Discussionmentioning
confidence: 99%
“…So we need to establish whether sufficient clinicians are in equipoise and willing to recruit and randomise patients to a RCT. There is growing evidence in favour of pilot studies involving collection of both quantitative and qualitative data prior to embarking on this type of definitive RCT [14]. …”
Section: Introductionmentioning
confidence: 99%
“…This study has identified differences in the way women perceive research studies involving different intervention arms. There have been a number of studies published looking at barriers to recruitment6, 14, 15 both from the physician and the patient perspective but no one has looked at the types of studies patients would be willing to participate in terms of specific alternative treatment modalities.…”
Section: Discussionmentioning
confidence: 99%